INDONESIAN ISLAMIC MOVEMENT OF WOMEN: A STUDY OF FATAYAT MUSLIMAT NU (1938-2013) - Hamidah Hamidah (State Islamic University North Sumatra, 2016)
Abstract: The purpose of this article is to examine the dynamics of Indonesian Muslim women's movement of a socio-historical study of the Moslem-Fatayat NU during the period 1938-2013. The socio-historical, Indonesian Islamic women's movement can exist not only from tahrirul mar'ah movement but also the influence of the feminist movement that developed in the Western world. The development of Moslem-Fatayat plays a strategic role in social transformation efforts. Transformation through a process of awareness that ran in